Estimation of spatial and temporal water requirements of grain amaranth using satellite, local and virtual weather stations datasets in Uganda - Kyagulanyi, Joseph; Kabenge, Isa; Banadda, Noble; Muyonga, John; Mulamba, Peter; Kiggundu, Nicholas (International Journal of Agricultural and Biological Engineering, 2016)
In this study, an integrated approach incorporating Remote Sensing (RS), Geographical Information System (GIS), local meteorological weather stations’ data and NASA’s virtual meteorological stations’ data were used to quantify Grain Amaranth (GA) water requirements in Uganda. Penman-Monieth method within CropWAT8 model and Surface Energy Balance Algorithm for Land (SEBAL) Model was used to quantify the evapotranspiration. Normalized Difference Vegetation Index (NDVI), daily spatial distribution of Evapotranspiration (ET), Land Surface Temperature (LST) and surface albedo were extracted from satellite imagery. The ratio of effective rainfall (Pe) to Potential Evapotranspiration (PET) – (Pe/PET) and time series for NDVI were computed to determine the growth stage of GA in different areas. The GA water demand was the highest in Karamoja sub-region (467.5 mm/season) and the lowest in Tororo (174.1 mm/season). The growing season for GA in most areas of Uganda was from March to December. Estimation of evapotranspiration in Karamoja sub-region with SEBAL model corresponded to the NDVI extracted, especially for highly vegetated areas. CROPWAT indicated that if GA was planted during the late September and early October in Karamoja sub-region, despite the decreasing moisture levels, the crop could have sufficient water supply during emergence to maturity. The ability to utilize low available moisture levels makes GA a potential crop to bridge the gap (due to the elongated drought) for the food production cycle in Karamoja sub-region. Keywords: Grain Amaranth, water requirement, remote sensing, SEBAL, evapotranspiration, Uganda DOI: 10.3965/j.ijabe.20160902.1676 Citation: Kyagulanyi J, Kabenge I, Banadda N, Muyonga J, Mulamba P, Kiggundu N. Estimation of spatial and temporal water requirements of grain amaranth using satellite, local and virtual weather stations datasets in Uganda. Int J Agric & Biol Eng, 2016; 9(2): 85－97.